2022
DOI: 10.18632/aging.203847
|View full text |Cite
|
Sign up to set email alerts
|

A catalogue of omics biological ageing clocks reveals substantial commonality and associations with disease risk

Abstract: Biological age (BA), a measure of functional capacity and prognostic of health outcomes that discriminates between individuals of the same chronological age (chronAge), has been estimated using a variety of biomarkers. Previous comparative studies have mainly used epigenetic models (clocks), we use ~1000 participants to compare fifteen omics ageing clocks, with correlations of 0.21-0.97 with chronAge, even with substantial sub-setting of biomarkers. These clocks track common aspects of ageing with 95% of the v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 74 publications
2
31
0
Order By: Relevance
“…It is hypothesized that biological age, influenced by different molecular hallmarks such as telomere shortening, genomic instability and cellular senescence, gives rise to age-related disease risk. Therefore, biological age is a much more potent prognostic tool for health outcomes than chronological age, and more importantly, it can be reversed ( Jurić et al, 2020 ; Greto et al, 2021 ; Macdonald-Dunlop et al, 2022 ). Since this notion has been proposed, different predictors of biological age, termed aging clocks, were constructed using various methods ( Horvath et al, 2020 ; Macdonald-Dunlop et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hypothesized that biological age, influenced by different molecular hallmarks such as telomere shortening, genomic instability and cellular senescence, gives rise to age-related disease risk. Therefore, biological age is a much more potent prognostic tool for health outcomes than chronological age, and more importantly, it can be reversed ( Jurić et al, 2020 ; Greto et al, 2021 ; Macdonald-Dunlop et al, 2022 ). Since this notion has been proposed, different predictors of biological age, termed aging clocks, were constructed using various methods ( Horvath et al, 2020 ; Macdonald-Dunlop et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, biological age is a much more potent prognostic tool for health outcomes than chronological age, and more importantly, it can be reversed ( Jurić et al, 2020 ; Greto et al, 2021 ; Macdonald-Dunlop et al, 2022 ). Since this notion has been proposed, different predictors of biological age, termed aging clocks, were constructed using various methods ( Horvath et al, 2020 ; Macdonald-Dunlop et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work by Macdonald-Dunlop et al performed a thorough comparison of 15 different omics-based clocks. The authors found that, while some clocks correlated well with specific disease risk factors (e.g., systolic blood pressure and cortisol), others were more prognostic of age-related disease incidence and appeared to better reflect the generalized effects of aging (Macdonald-Dunlop et al, 2022). Moreover, there is an interesting relationship between accuracy and usability.…”
Section: Outstanding Questions and Limitations In The Fieldmentioning
confidence: 99%
“…The benefits of reducing the number of features down to single digit or low double digit sites also improves accuracy. Macdonald-Dunlop and colleagues showed that for -omics based aging clocks, those with lower model complexity (built from fewer principal components) had greater accuracy [ 18 ]. While fewer CpG sites may leave the lone few features more vulnerable to confounding effects, the clocks of several hundred CpGs suffer from too much noise rather than signal for age predictions.…”
Section: Introductionmentioning
confidence: 99%